Could the 2017 ILAE and the four-dimensional epilepsy classifications be merged to a new "Integrated Epilepsy Classification"?. (May 2020) - Rosenow, Felix; Akamatsu, Naoki; Bast, Thomas; Bauer, Sebastian; Baumgartner, Christoph; Benbadis, Selim; Bermeo-Ovalle, Adriana; Beyenburg, Stefan; Bleasel, Andrew; Bozorgi, Alireza; Brázdil, Milan; Carreño, Mar; et al.
Highlights: The differences of the two epilepsy classifications (ECs) in use have been discussed extensively. Here we reviewed and assessed the concordance between these two approaches that has evolved over time. We considered whether a classification incorporating the best aspects of the two approaches is feasible. A concrete proposal showing how such a compromise could be accomplished is proposed and discussed. The suggested "Integrated EC" includes five categories derived both classification systems. Abstract: Over the last few decades the ILAE classifications for seizures and epilepsies (ILAE-EC) have been updated repeatedly to reflect the substantial progress that has been made in diagnosis and understanding of the etiology of epilepsies and seizures and to correct some of the shortcomings of the terminology used by the original taxonomy from the 1980s. However, these proposals have not been universally accepted or used in routine clinical practice. During the same period, a separate classification known as the "Four-dimensional epilepsy classification" (4D-EC) was developed which includes a seizure classification based exclusively on ictal symptomatology, which has been tested and adapted over the years. The extensive arguments for and against these two classification systems made in the past have mainly focused on the shortcomings of each system, presuming that they are incompatible. As a further more detailed discussion of the differences seemed relatively unproductive, we here review and assess the concordance between these two approaches that has evolved over time, to consider whether a classification incorporating the best aspects of the two approaches is feasible. To facilitate further discussion in this direction we outline a concrete proposal showing how such a compromise could be accomplished, the "Integrated Epilepsy Classification". This consists of five categories derived to different degrees from both of the classification systems: 1) a "Headline" summarizing localization and etiology for the less specialized users, 2) "Seizure type(s)", 3) "Epilepsy type" (focal, generalized or unknown allowing to add the epilepsy syndrome if available), 4) "Etiology", and 5) "Comorbidities & patient preferences".